Bifunctional catalyst as well as preparation method and application thereof
By loading the high-entropy alloy on a single-atom catalyst and using carbon-thermal impact technology to achieve uniform distribution, HEA@FeNC dual-function catalyst is formed, the efficiency and utilization problems of the single-atom catalyst and high-entropy alloy catalyst are solved, and efficient synergistic catalysis and stability improvement are achieved.
Patent Information
- Application Number
- CN202411889962.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the prior art, single atom catalysts limit the efficiency of multi-step reactions due to a single type of active center, while high-entropy alloy catalysts have a small specific surface area and low active site utilization, making it difficult to widely use in zinc air batteries.
By loading the high-entropy alloy on a single atom catalyst, the carbon-thermal impact technology is used to achieve rapid formation and uniform distribution of the high-entropy alloy on a single atom, forming a dual-functional catalyst of HEA@FeNC, combining the advantages of high-entropy alloys and single atom catalysts to achieve synergistic catalysis.
It realizes efficient synergistic catalysis of dual-function catalysts, improves catalytic activity and stability, and significantly improves the performance of zinc air batteries.
Smart Images

Figure CN119764466A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery material preparation, and specifically relates to a bifunctional catalyst and a preparation method and application thereof. Background Art
[0002] In recent decades, the large-scale development and application of fossil fuels have caused their reserves to drop sharply. At the same time, the large-scale use of fuels such as coal and oil has also led to increased environmental pollution. Therefore, finding new technologies for storing and converting energy is a current research hotspot. Rechargeable zinc-air batteries (RZABs) are a green, safe and high-power energy supply device that can greatly reduce people's dependence on fossil fuels and solve today's environmental problems. Oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) occur at the air electrode of the battery device. Bifunctional oxygen electrocatalysts are one of the core factors that determine the efficiency and performance of RZABs. Nanomaterials with high-efficiency catalytic activity show good application prospects in RZABs.
[0003] For a long time, Pt-based and Ru-based catalysts have been the most relied-on materials for ORR / OER, because these two types of noble metal catalysts have moderate adsorption and desorption strengths for oxygen-containing intermediates, thus becoming the benchmark catalysts for ORR and OER. However, these two noble metals are extremely low in abundance in nature, expensive, and have poor durability and anti-poisoning properties, which severely limit their widespread application. Among the many non-noble metal catalysts, atomically dispersed transition metal-nitrogen-carbon (MNC, M=Ni, Fe, Co, etc.) materials have attracted widespread attention due to their catalytic activity similar to that of noble metals. Compared with traditional oxygen electrocatalysts, the active site utilization rate of atomic-level catalysts is almost 100%, which greatly reduces the preparation and use costs of catalysts; by precisely controlling the microstructure of the material and the distribution of atomic sites, the stability and catalytic activity of nanomaterials can be greatly improved.
[0004] At present, there are many reports on single-atom catalysts. The Chinese patent application number 202010564117.8 discloses a single-atom cobalt-loaded nitrogen-doped graphite-like carbon cathode catalyst for metal-air batteries. This method prepares a single-atom cobalt-loaded graphite-like carbon material. At a voltage of 0.5V, the current density of the catalyst can reach 290mA·cm -2; Chinese patent application number 202310580148.6 discloses a composite catalyst in which metal nanoparticles and single atoms coexist. Although its catalyst performance is good, the atomic utilization rate is limited. In addition, there are reports on the use of high entropy alloy catalysts in zinc-air batteries. In addition to high configurational entropy, high entropy alloy nanoparticles also have lattice distortion, hysteresis diffusion and cocktail effect. These effects work together to make high entropy alloy nanoparticles have good multifunctional catalytic potential. For example, Chinese patent application number 202410299244.8 discloses a high entropy alloy composite material and its Joule heat preparation method and application in zinc-air batteries. However, when the high entropy alloy is used for catalysis, most of the atoms are located inside the alloy and cannot participate in the catalytic reaction.
[0005] In summary, single-atom catalysts limit the efficiency of multi-step reactions due to a single type of active center, and high-entropy alloy catalysts have active sites with rich components, but compared with single-atom catalysts, they have a smaller specific surface area and a low utilization rate of active sites. In view of this, the present invention is proposed. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a bifunctional catalyst and a preparation method and application thereof, combining the advantages of high entropy alloys and single-atom catalysts, and utilizing thermal shock pyrolysis to obtain a bifunctional catalyst with uniform distribution, good catalytic activity and high stability.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a bifunctional catalyst, wherein ZIF-8 is first subjected to pyrolysis treatment, then impregnated with a loaded iron source and then subjected to carbon thermal shock treatment, and finally impregnated with a loaded soluble metal salt and then subjected to carbon thermal shock treatment.
[0009] In the above technical solution, the applicant proposed a strategy of loading high entropy alloys on single atoms to solve the trade-off problem between the two. High entropy alloys as carriers can effectively anchor single atoms to prevent agglomeration and loss. At the same time, the components of high entropy alloys are adjustable to achieve fine control of performance. The combination of the two has a synergistic catalytic effect. Single atoms provide precise active sites, and high entropy alloys provide a diverse local environment, which can achieve efficient synergy of single-step and multi-step reactions.
[0010] Further, the preparation method provided by the present invention uses carbon thermal shock to achieve rapid formation and uniform distribution of high entropy alloy on single atoms, and obtains high entropy alloy @ carbon matrix bifunctional catalyst with uniform distribution by short-time and precise thermal shock pyrolysis of spatially confined precursors (such as multi-metal organic framework MOF). Rapid heating and cooling help prevent element segregation and promote uniform distribution. At the same time, rapid pyrolysis can inherit the multi-scale porous structure of precursors such as MOF to form single atoms with unique porous structures connected by three-dimensional carbon frameworks, which is conducive to the exposure of more active sites and the penetration of electrolytes; and single atoms are crucial to the anchoring of subsequent high entropy alloys (HEA) to improve the bifunctional activity and stability of the catalyst.
[0011] Specifically, the above preparation method comprises the following steps:
[0012] (1) Preparation of ZIF-8;
[0013] (2) Preparation of NC: The ZIF-8 prepared in step (1) is subjected to pyrolysis treatment to obtain NC material;
[0014] (3) dripping the iron source solution onto the NC material obtained in step (2), grinding, drying, and then performing carbon thermal shock treatment to obtain FeNC single-atom material;
[0015] (4) dripping a soluble metal salt solution onto the FeNC single atom material obtained in step (3), grinding, drying, and then subjecting the material to carbon thermal shock treatment to obtain the bifunctional catalyst.
[0016] In the above technical solution, the preparation of ZIF-8 in step (1) can be obtained by a preparation method in the prior art. For example, it can be prepared by a method comprising the following steps:
[0017] The zinc source was added into methanol and subjected to ultrasonic treatment to obtain solution A;
[0018] The organic ligand is added to methanol and subjected to ultrasonic treatment to obtain solution B;
[0019] After mixing solution A and solution B, continue ultrasonic treatment and keep stirring to obtain solution C;
[0020] After washing, centrifuging and drying the solution C, ZIF-8 was obtained.
[0021] As a preferred embodiment of the technical solution of the present invention, in the preparation process of ZIF-8 provided above, the zinc source is Zn(NO3)2·6H2O, and the concentration of solution A is 0.1-0.4 mol / L; it can be understood that the concentration of solution A can be a value among 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L or any value within the above range, and those skilled in the art can flexibly select;
[0022] The organic ligand is selected from one or more of imidazole, dimethylimidazole, imidazole-2-carboxaldehyde, benzimidazole, 5-methylbenzimidazole, and 2-aminobenzimidazole, and the concentration of solution B is 0.4-1.6 mol / L; it can be understood that the organic ligand can be actually selected according to the actual needs, preferably, dimethylimidazole is selected as the organic ligand; the concentration of solution B can be 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L or any value within the above range, and those skilled in the art can flexibly select;
[0023] The stirring speed is 800-1500rpm, and the stirring treatment time is 6-48h; the stirring is preferably magnetic stirring. It can be understood that the stirring speed can be a value among 800rpm, 900rpm, 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm, 1500rpm or any value within the above range, and the stirring time can be a value among 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h or any value within the above range, and those skilled in the art can flexibly choose;
[0024] The centrifugal speed is 5000-10000 rpm, and the centrifugal time is 1-5 min. It is understandable that the centrifugal speed can be 5000 rpm, 5100 rpm, 5200 rpm, 5300 rpm, 5400 rpm, 5500 rpm, 5600 rpm, 5700 rpm, 5800 rpm, 5900 rpm, 6000 rpm, 6100 rpm, 6200 rpm, 6300 rpm, 6400 rpm, 6500 rpm, 6600 rpm, 6700 rpm, 6800 rpm, 6900 rpm, 7000 rpm, 7100 rpm, 7200 rpm, 7300 rpm, 7400 rpm, 7500 rpm, 7600 rpm, 7700 rpm, 7800 rpm, 7900 rpm, etc. The centrifugal time can be 1min, 2min, 3min, 4min, 5min or any value in the above range, and those skilled in the art can flexibly select. It should be particularly noted that the washing of solution C is to wash away impurities such as uncoordinated ligands, and the detergent can be at least one of methanol, ethanol, isopropanol and N,N-dimethylformamide.
[0025] As a preferred embodiment of the technical solution of the present invention, the pyrolysis treatment temperature of ZIF-8 is 900-1100°C, the heating rate is 5-10°C / min, and the holding time is 30-60min. It is understandable that the pyrolysis treatment temperature can be 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C or any value within the above range, and the heating rate can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value within the above range, and those skilled in the art can flexibly select. It should be particularly emphasized that the above-mentioned pyrolysis treatment process can be carried out under an atmosphere, and the atmosphere can be selected from N2 or Ar.
[0026] As a preferred embodiment of the technical solution of the present invention, the iron source solution is obtained by dissolving FeCl3·6H2O in ethanol, the molar concentration of iron atoms is 0.1-0.3 mol / L, and the impregnation loading amount is 0.01-5wt%.
[0027] As a preferred embodiment of the technical solution of the present invention, the carbon thermal shock condition in step (3) is: pulse heating treatment is carried out under nitrogen or argon protection, the current is 10-60A, and the treatment time is 10ms-1s. It should be particularly emphasized that pulse heating treatment is a prior art method and can be carried out with reference to patent document CN114361634A. Specifically, a pulse power supply can be selected as the heating power supply, the pulse current waveform is a square wave, the voltage is 20-60V, the pulse time is adjusted by a relay, the pulse frequency is 0.1-1HZ, the heating time accounts for 1-5%, and the number of pulses is 1-5 times.
[0028] As a preferred embodiment of the technical solution of the present invention, the metals in the soluble metal salt solution are selected from at least five of Fe, Co, Ni, Mn, Cr, Mo, Zn, Sn, and W, with a total concentration of 0.02 to 0.5 mol / L, and an impregnation load of 0.01 to 5 wt %. Preferably, the atomic ratios of the metal salts in the soluble metal salt solution are the same.
[0029] As a preferred embodiment of the technical solution of the present invention, the carbon thermal shock condition in step (3) is: pulse heating treatment is performed under nitrogen or argon protection, the current is 10-60A, and the treatment time is 10ms-1s. Similarly, pulse heating treatment is a prior art method, which can be performed with reference to patent document CN114361634A. Specifically, a pulse power supply can be selected as a heating power supply, the pulse current waveform is a square wave, the voltage is 20-60V, the pulse time is adjusted by a relay, the pulse frequency is 0.1-1HZ, the heating time accounts for 1-5%, and the number of pulses is 1-5 times.
[0030] In a second aspect, the present invention aims to protect the bifunctional catalyst prepared by the above method.
[0031] In a third aspect, the present invention seeks to protect the use of the above-mentioned bifunctional catalyst in the preparation of OER / ORR electrocatalysts and the use of the above-mentioned catalyst in the preparation of zinc-air batteries.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The bifunctional catalyst provided by the present invention proposes a strategy of loading a high entropy alloy on a single atom to solve the trade-off problem between the two. The high entropy alloy as a carrier can effectively anchor the single atom to prevent agglomeration and loss. At the same time, the composition of the high entropy alloy is adjustable to achieve fine control of the performance. The combination of the two has a synergistic catalytic effect. The single atom provides precise active sites, and the high entropy alloy provides a diverse local environment. Efficient synergy of single-step and multi-step reactions can be achieved, making full use of the advantages of high entropy alloys and single-atom catalysts.
[0034] (2) The preparation method of the bifunctional catalyst provided by the present invention, through the rapid pyrolysis of carbon thermal shock, makes the carbon carrier inherit the multi-scale porous structure of MOF, forming a single-atom loaded HEA with a unique porous and layered structure connected by a three-dimensional carbon framework. Compared with the common bifunctional catalysts, the HEA@FeNC bifunctional catalyst prepared by the present invention not only has an adjustable HEA component, but also increases the specific surface area of the carbon carrier, thereby exposing more catalytic active sites, increasing the adsorption and activation efficiency of the reactants, and thus improving the catalytic activity.
[0035] (3) The bifunctional catalyst provided by the present invention improves the stability of the FeNC catalyst by introducing HEA, thereby greatly improving the stability of the bifunctional catalyst.
[0036] (4) The bifunctional catalyst provided by the present invention improves the OER performance of the FeNC catalyst by introducing HEA, and utilizes the synergistic effect of HEA+FeNC to improve the bifunctional activity.
[0037] (5) The HEA@FeNC bifunctional catalyst provided by the present invention is used in OER / ORR electrocatalysts and has high activity, with a half-wave potential of 0.9 V in ORR and 10 mA / cm in OER. -2 The overpotential is 280mV, △E(E J=10 - E 1 / 2 ) is 0.61V.
[0038] (6) The preparation method of the bifunctional catalyst provided by the present invention is simple, the preparation time is short, the composition is controllable, the process is stable and repeatable, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Surface morphology of ZIF-8 and NC materials of the present invention.
[0040] Figure 2 X-ray diffraction patterns of HEA@FeNC prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0041] Figure 3This is a surface morphology of the HEA@FeNC bifunctional catalyst prepared in Example 1 of the present invention.
[0042] Figure 4 This is the element distribution diagram of the HEA@FeNC bifunctional catalyst prepared in Example 1.
[0043] Figure 5 Graphs showing the LSV curves of different bifunctional catalyst materials of the present invention; wherein, graph (a) is an OER performance test, and graph (b) is an ORR performance test.
[0044] Figure 6 This is a stability curve diagram of the bifunctional catalyst material of Example 1 of the present invention after 20K cycle testing.
[0045] Figure 7 This is a graph showing the cyclic charge and discharge stability of the bifunctional catalyst of Example 1 of the present invention and a commercial Pt / C+IrO2 zinc-air battery. DETAILED DESCRIPTION
[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] It should be noted that the types of metal salts in the HEA precursor can be at least five of Fe, Co, Ni, Mn, Cr, Mo, Zn, Sn, W, etc. Therefore, the HEA@FeNC bifunctional catalyst prepared by the carbon thermal shock method of the present invention is universal and can be used to prepare various combinations of HEA@single atom catalysts, and can also be used to prepare quaternary, ternary and binary alloy@single atom catalysts.
[0048] Example 1
[0049] A method for synthesizing a HEA@FeNC bifunctional catalyst comprises the following steps:
[0050] (1) Preparation of ZIF-8: Dissolve 6.78 g Zn(NO3)2·6H2O in 300 mL methanol solution and 7.88 g dimethylimidazole in 300 mL methanol solution, ultrasonicate them in an ultrasonic machine for 15 min until they are completely dissolved in the methanol solution; then pour the dimethylimidazole methanol solution into the zinc nitrate methanol solution and continue ultrasonicating for 15 min. Place the mixed solution on a magnetic stirrer and stir at 1200 rpm for 12 h until a milky white suspension appears; centrifuge the suspension, wash it three times, and dry it in a vacuum dryer at 60°C for 360 min to obtain ZIF-8;
[0051] (2) Preparation of NC: 300 mg of ZIF-8 was placed in a magnetic boat, annealed at 1000 °C in an argon atmosphere for 30 min, and then naturally cooled to room temperature to obtain nitrogen-doped carbon with MOF morphology;
[0052] (3) Preparation of FeNC: 267uL of 0.2mol / L FeCl3·6H2O ethanol solution was impregnated onto 100mg of the nitrogen-doped carbon obtained in step (2), and the mixture was manually ground in a mortar until the ethanol was completely evaporated, and the FeNC precursor was collected; the FeNC precursor was placed on a 1.5cm*4cm carbon cloth, and the carbon cloth was clamped between the two ends of a pulse power supply and subjected to carbon thermal shock at 1800℃ for 100ms in an argon atmosphere to obtain a FeNC single atom catalyst;
[0053] (4) Preparation of HEA@FeNC: 25uL of 0.2mol / L Fe, Co, Ni, Mo, and Zn ethanolate solution (with the same atomic ratio of each metal element) was impregnated and loaded on 100mg of FeNC single atom catalyst obtained in step (3), and manually ground in a mortar until the ethanol was completely evaporated, and the HEA@FeNC precursor was collected; similarly, the HEA@FeNC precursor was subjected to the same carbon thermal shock as in step (3), but the temperature was changed to 1300°C to obtain the HEA@FeNC bifunctional catalyst.
[0054] Example 2
[0055] A method for synthesizing a HEA@FeNC bifunctional catalyst comprises the following steps:
[0056] (1) Preparation of ZIF-8: Dissolve 6.78 g Zn(NO3)2·6H2O in 300 mL methanol solution and 7.88 g dimethylimidazole in 300 mL methanol solution, ultrasonicate them in an ultrasonic machine for 15 min until they are completely dissolved in the methanol solution; then pour the dimethylimidazole methanol solution into the zinc nitrate methanol solution and continue ultrasonicating for 15 min. Place the mixed solution on a magnetic stirrer and stir at 1200 rpm for 12 h until a milky white suspension appears; centrifuge the suspension, wash it three times, and dry it in a vacuum dryer at 60°C for 360 min to obtain ZIF-8;
[0057] (2) Preparation of NC: 300 mg of ZIF-8 was placed in a magnetic boat, annealed at 1000 °C in an argon atmosphere for 30 min, and then naturally cooled to room temperature to obtain nitrogen-doped carbon with MOF morphology;
[0058] (3) Preparation of FeNC: 267 uL of 0.2 mol / L FeCl3·6H2O ethanol solution was impregnated onto 100 mg of the nitrogen-doped carbon obtained in step (2) of Example 1, and the mixture was manually ground in a mortar until the ethanol was completely evaporated, and the FeNC precursor was collected; the FeNC precursor was placed on a 1.5 cm*4 cm carbon cloth, and the carbon cloth was clamped between the two ends of a pulse power supply and subjected to carbon thermal shock at 1300°C for 300 ms in an argon atmosphere to obtain a FeNC single atom catalyst.
[0059] (4) Preparation of HEA@FeNC: 25uL 0.2 mol / L Fe, Co, Ni, Mn, Cr ethanolate solution (the atomic ratio of each metal element is the same) was impregnated and loaded on the 100mg FeNC single atom catalyst obtained in step (3), and manually ground in a mortar until the ethanol evaporated completely, and collected as the HEA@FeNC precursor. Similarly, the HEA@FeNC precursor was subjected to the same carbon thermal shock as in step (3), at a temperature of 1300°C and a pyrolysis time of 200ms to obtain the HEA@FeNC bifunctional catalyst.
[0060] Example 3
[0061] A method for synthesizing a HEA@FeNC bifunctional catalyst comprises the following steps:
[0062] (1) Preparation of ZIF-8: Dissolve 6.78 g Zn(NO3)2·6H2O in 300 mL methanol solution and 7.88 g dimethylimidazole in 300 mL methanol solution, ultrasonicate them in an ultrasonic machine for 15 min until they are completely dissolved in the methanol solution; then pour the dimethylimidazole methanol solution into the zinc nitrate methanol solution and continue ultrasonicating for 15 min. Place the mixed solution on a magnetic stirrer and stir at 1200 rpm for 12 h until a milky white suspension appears; centrifuge the suspension, wash it three times, and dry it in a vacuum dryer at 60°C for 360 min to obtain ZIF-8;
[0063] (2) Preparation of NC: 300 mg of ZIF-8 was placed in a magnetic boat, annealed at 1000 °C in an argon atmosphere for 30 min, and then naturally cooled to room temperature to obtain nitrogen-doped carbon with MOF morphology;
[0064] (3) Preparation of FeNC: 267uL of 0.2mol / L FeCl3·6H2O ethanol solution was impregnated onto 100mg of the nitrogen-doped carbon obtained in step (2), and the mixture was manually ground in a mortar until the ethanol was completely evaporated, and the FeNC precursor was collected; the FeNC precursor was placed on a 1.5cm*4cm carbon cloth, and the carbon cloth was clamped between the two ends of a pulse power supply and subjected to carbon thermal shock at 1800℃ for 100ms in an argon atmosphere to obtain a FeNC single atom catalyst;
[0065] (4) Preparation of HEA@FeNC: 100 μL of 0.2 mol / L Fe, Co, Ni, Mo, and Zn ethanolate solution (with the same atomic ratio of each metal element) was impregnated onto 100 mg of FeNC single atom catalyst, and the mixture was manually ground in a mortar until the ethanol was completely evaporated. The HEA@FeNC precursor was collected. The HEA@FeNC precursor was placed on a 1.5 cm*4 cm carbon cloth, which was clamped between the two ends of a pulse power supply and subjected to carbon thermal shock at 1300°C for 100 ms in an argon atmosphere to obtain the HEA@FeNC bifunctional catalyst.
[0066] Comparative Example 1
[0067] In the catalyst provided in Comparative Example 1, HEA is not anchored to FeNC, but carbon black is used. Specifically, the catalyst of HEA@C using carbon black includes the following steps:
[0068] 25uL of 0.2mol / L Fe, Co, Ni, Mo, and Zn ethanolate solution (the atomic ratio of each metal element is the same) is impregnated and loaded on 100mg of carbon black, placed in a mortar and manually ground until the ethanol is completely evaporated, and the HEA@C precursor is collected; the HEA@C precursor is placed on a 1.5cm*4cm carbon cloth, and the carbon cloth is clamped between the two ends of a pulse power supply and carbon thermally shocked at 1300℃ for 100ms in an argon atmosphere to obtain a HEA@C catalyst.
[0069] Comparative Example 2
[0070] In Comparative Example 2, no carbon thermal shock treatment is used to treat HEA. Specifically, a catalyst is prepared, comprising the following steps:
[0071] (1) Preparation of ZIF-8: Dissolve 6.78 g Zn(NO3)2·6H2O in 300 mL methanol solution and 7.88 g dimethylimidazole in 300 mL methanol solution, ultrasonicate them in an ultrasonic machine for 15 min until they are completely dissolved in the methanol solution; then pour the dimethylimidazole methanol solution into the zinc nitrate methanol solution and continue ultrasonicating for 15 min. Place the mixed solution on a magnetic stirrer and stir at 1200 rpm for 12 h until a milky white suspension appears; centrifuge the suspension, wash it three times, and dry it in a vacuum dryer at 60°C for 360 min to obtain ZIF-8;
[0072] (2) Preparation of NC: 300 mg of ZIF-8 was placed in a magnetic boat, annealed at 1000 °C in an argon atmosphere for 30 min, and then naturally cooled to room temperature to obtain nitrogen-doped carbon with MOF morphology;
[0073] (3) Preparation of FeNC: 267uL of 0.2mol / L FeCl3·6H2O ethanol solution was impregnated onto 100mg of the nitrogen-doped carbon obtained in step (2), and the mixture was manually ground in a mortar until the ethanol was completely evaporated, and the FeNC precursor was collected; the FeNC precursor was placed on a 1.5cm*4cm carbon cloth, and the carbon cloth was clamped between the two ends of a pulse power supply and subjected to carbon thermal shock at 1800℃ for 100ms in an argon atmosphere to obtain a FeNC single atom catalyst;
[0074] (4) Preparation of catalyst: 25uL of 0.2mol / L Fe, Co, Ni, Mo, Zn ethanolate solution (the atomic ratio of each metal element is the same) was impregnated and loaded on 100mg FeNC, and the mixture was manually ground in a mortar until the ethanol was completely evaporated. The precursor was collected; the precursor was placed in a magnetic boat and placed in a tubular furnace. Under an argon atmosphere, the temperature was increased at a rate of 10℃ / min to 1300℃, kept for 1h, and then naturally cooled to room temperature to obtain the catalyst.
[0075] The relevant performance tests were carried out on the embodiments and comparative examples, and the results are shown in Figure 1 to Figure 4 .
[0076] Figure 1 Figure 2 shows the surface morphology of ZIF-8 and nitrogen-doped carbon obtained after pyrolysis. It can be seen from the figure that the nitrogen-doped carbon retains the original morphology, which is attributed to the relatively mild pyrolysis conditions in the tube furnace.
[0077] Figure 2 Bifunctional X-ray diffraction patterns (XRD) were prepared for Example 1, Comparative Example 1 and Comparative Example 2. XRD showed that there were two main phases, Co and Mo2C, in the sample, corresponding to the standard cards Co 15-0806 and Mo2C 72-1683. Example 1 shows the simplest and clearest diffraction peaks, indicating that a relatively single phase structure with good crystallinity has been formed. In contrast, both Comparative Examples 1 and 2 show more complex peaks and additional diffraction peaks, indicating that there are more phase separations. From the design concept of high entropy alloys, the formation of a simple solid solution phase should be pursued, so the synthesis of Example 1 is the most successful. At the same time, the background of Example 1 is smooth and the peak is clear, indicating that the single atom dispersion of Fe-NC is good.
[0078] Figure 3 This is the surface morphology of the HEA@FeNC bifunctional catalyst synthesized in Example 1. The catalyst retains the structure of MOF, which is attributed to the preparation of rapid temperature rise and fall in milliseconds. At the same time, the carbon support is partially graphitized, so the carbon thermal shock not only retains a high specific surface area, but also increases the conductivity.
[0079] Figure 4This is the element distribution diagram of the HEA@FeNC bifunctional catalyst prepared in this Example 1. It can be seen from the figure that the FeCoNiMoZn@FeNC multi-stage high entropy alloy catalyst was successfully prepared on FeNC by the carbon thermal shock method.
[0080] In order to evaluate the bifunctional performance of the catalysts in Example 1 and Comparative Examples 1 and 2, an OER / ORR catalytic performance test was performed on them, and the catalysts in Example 1 and Comparative Examples 1 and 2 were assembled into zinc-air batteries to perform zinc-air battery performance tests. The specific test steps and results are as follows:
[0081] (1) OER performance test: 5 mg of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 were mixed with 500 uL isopropanol, 500 uL deionized water and 20 uL Nafion respectively, and then ultrasonicated for 20 min until the catalyst was evenly dispersed into Ink. 50 uL Ink was evenly dropped on 0.5*1 cm carbon paper, and after drying, it was clamped on the electrode clamp as the working electrode, Hg / HgO as the reference electrode, Pt sheet as the counter electrode, and 1M KOH as the electrolyte for electrochemical testing. The potential interval was set to 0-1 V, the scan rate was 10 mV / s, and the LSV performance test was performed. The performance curve is shown in the figure. Figure 5 As shown in (a), it can be seen from the figure that compared with Comparative Examples 1-2, the HEA@Fe-NC bifunctional catalyst prepared in Example 1 has the best OER activity, 10 mA / cm -2 The overpotential is 280mV.
[0082] (2) ORR performance test: 5 mg of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 were mixed with 500 uL isopropanol, 500 uL deionized water and 20 uL Nafion respectively, and then ultrasonicated for 20 min until the catalyst was evenly dispersed into Ink. 10 uL Ink was evenly dropped onto the clean glassy carbon electrode head, and after drying, it was used as the working electrode, Hg / HgO as the reference electrode, Pt sheet as the counter electrode, and 0.1 M KOH as the electrolyte for electrochemical testing. Before the test, high-purity O2 was continuously introduced into the electrolyte for 30 min, and CV (cyclic voltammetry) activation was performed, and the scan speed was controlled at 100 Mv s -1 After CV activation, LSV (linear cyclic voltammetry) was performed with a scan rate of 5 mV s -1 , IR compensation is 90%, and the disk electrode rotation speed is 1600rpm. Figure 5 (b) The scanning rate of Example 1, Comparative Example 1 and Comparative Example 2 in an O2-saturated 0.1 M KOH solution was 5 mV s -1LSV curves under the conditions of 90% IR compensation and a disk electrode rotation speed of 1600 rpm. It can be seen from the figure that compared with Comparative Examples 1-2, the HEA@FeNC bifunctional catalyst prepared in Example 1 has the best ORR activity with a half-wave potential of 0.9 vs. RHE. The durability of Example 1 was evaluated in an O2-saturated 0.1M KOH electrolyte using an accelerated durability test (ADT), and the catalyst showed significant stability. 1 / 2 After 20,000 cycles, the voltage decayed by only 5 mV (see Figure 6 ).
[0083] (3) Zinc-air battery test: 5 mg of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 were mixed with 500 uL isopropanol, 500 uL deionized water and 20 uL Nafion respectively, and then ultrasonicated for 20 min until the catalyst was uniformly dispersed into Ink. The Ink was dropped onto a 2*2 cm conductive carbon paper with a loading of 1 mg / cm -2 , and drying the carbon paper; then assembling the prepared HEA@FeNC into a zinc-air battery, specifically using zinc sheet as the negative electrode, HEA@FeNC as the positive electrode catalyst, and 6M KOH containing 0.2MZn(OAc)2 as the electrolyte; setting the current density to 5mA / cm 2 , charging time is 15min, discharging time is 15min, the battery has long-term charge and discharge cycle stability, such as Figure 7 As shown, Example 1 was able to stably operate for 1640 cycles within 820 hours; however, the commercial Pt / C+IrO2 completely failed after 170 hours of operation.
[0084] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a bifunctional catalyst, characterized in that: The ZIF-8 was first pyrolyzed, then impregnated with an iron source and then subjected to a carbon thermal shock treatment, and finally impregnated with a soluble metal salt and then subjected to a carbon thermal shock treatment.
2. The method for preparing a bifunctional catalyst according to claim 1, characterized in that: The steps include: (1) Preparation of ZIF-8; (2) Preparation of NC: The ZIF-8 prepared in step (1) is subjected to pyrolysis treatment to obtain NC material; (3) dripping the iron source solution onto the NC material obtained in step (2), grinding, drying, and then performing carbon thermal shock treatment to obtain FeNC single-atom material; (4) dripping a soluble metal salt solution onto the FeNC single atom material obtained in step (3), grinding, drying, and then subjecting the material to carbon thermal shock treatment to obtain the bifunctional catalyst.
3. A method for preparing a bifunctional catalyst according to claim 1 or 2, characterized in that: The preparation of ZIF-8 includes the following steps: The zinc source was added into methanol and subjected to ultrasonic treatment to obtain solution A; The organic ligand is added to methanol and subjected to ultrasonic treatment to obtain solution B; After mixing solution A and solution B, continue ultrasonic treatment and keep stirring to obtain solution C; After washing, centrifuging and drying the solution C, ZIF-8 was obtained.
4. The preparation method according to claim 3, characterized in that: The zinc source is Zn(NO3)2·6H2O, and the concentration of solution A is 0.1-0.4 mol / L; The organic ligand is selected from one or more of imidazole, dimethylimidazole, imidazole-2-carboxaldehyde, benzimidazole, 5-methylbenzimidazole, and 2-aminobenzimidazole, and the concentration of solution B is 0.4-1.6 mol / L; The stirring speed is 800-1500 rpm, and the stirring treatment time is 6-48 hours; The centrifugal speed is 5000-10000 rpm, and the centrifugal time is 1-5 min.
5. The method for preparing a bifunctional catalyst according to claim 1 or 2, characterized in that: The pyrolysis treatment temperature of ZIF-8 is 900-1100°C, the heating rate is 5-10°C / min, and the insulation time is 30-60min.
6. The method for preparing a bifunctional catalyst according to claim 2, characterized in that: The iron source solution is obtained by dissolving FeCl3·6H2O in ethanol, the molar concentration of iron atoms is 0.1-0.3 mol / L, and the impregnation loading amount is 0.01-5 wt%.
7. A method for preparing a bifunctional catalyst according to 6, characterized in that: The carbon thermal shock conditions in step (3) are: pulse heating treatment under nitrogen or argon protection, the current is 10 to 60A, and the treatment time is 10ms to 1s.
8. A method for preparing a bifunctional catalyst according to claim 1 or 2, characterized in that: The metals in the soluble metal salt solution are selected from at least five of Fe, Co, Ni, Mn, Cr, Mo, Zn, Sn and W, with a total concentration of 0.02 to 0.5 mol / L and an impregnation loading of 0.01 to 5 wt%.
9. A method for preparing a bifunctional catalyst according to 8, characterized in that: The carbon thermal shock conditions in step (3) are: pulse heating treatment under nitrogen or argon protection, the current is 10 to 60A, and the treatment time is 10ms to 1s.
10. The bifunctional catalyst prepared by the method according to any one of claims 1 to 9.
11. Use of the bifunctional catalyst according to claim 10 in preparing a zinc-air battery.
Citation Information
Patent Citations
Monatomic cobalt-loaded nitrogen-doped graphite-like carbon cathode catalyst for rechargeable zinc-air battery and preparation method of monatomic cobalt-loaded nitrogen-doped graphite-like carbon cathode catalyst
CN111682224A
Efficient stripping method of battery positive / negative electrode material
CN114361634A
Fe-based metal-organic framework derived metal nanoparticle / monatomic composite catalyst as well as preparation method and application thereof
CN116726925A
High-entropy alloy composite material and Joule thermal preparation method and application thereof
CN118186463A
Method for preparing self-supporting monatomic catalyst by rapid high-temperature thermal shock method
CN116732542A